Neuro-cognitive performance in patients with schizophrenia: a cross-sectional study in a psychiatric clinic of a University Hospital - Ibrahim, Normala; Abdul Rahman, Abdul Hamid; Shah, Shamsul Azhar (Faculty of Medicine and Health Sciences, Universiti Putra Malaysia, 2009)
Introduction: Poor neuro-cognitive performance in patients with schizophrenia has been described as a core symptom of the illness and is shown to be associated with poor psycho-social functioning. Management of schizophrenia has shifted its focus to treat this deficit apart from only emphasising on positive and negative symptoms, as it will subsequently improve patient functioning and outcome. Objective: The study aims to determine the proportion of neuro-cognitive impairment in patients with schizophrenia in a psychiatric clinic in Hospital Universiti Kebangsaan Malaysia and factors that are likely to be associated with the impairment. Method: Across-sectional study design was conducted in this hospital-based study and subjects were randomly chosen from the psychiatric clinic. Rey Auditory Verbal Learning Test (RAVLT), Digit Forward and Backward (DF and DB), Trail Making Test (TMT) and Verbal Fluency Test (VF) were used to assess subjects' neuro-cognitive performance that measured their verbal memory and executive functioning of the brain. Results: The proportion of neuro-cognitive impairment is estimated at about 80% in patients with schizophrenia in this hospital-based study. A higher percentages of respondents had abnormal scores for RAVLT1, RAVLT5 and RAVLTB tests(75.6%, 68.3% and 82.9% respectively). The majority of respondents had normal scores for DF, VF tests (80.5% and 73.2% respectively), and about 51.2% of respondents had normal scores for DB test. For TMT, overall performance of respondents in Set A and B was poor. The mean duration of time taken to complete both sets was longer than that of a normal population based on age group: (age group: 18-39 years; TMT A 68.98 vs 40 seconds; TMT B 174.09 vs 90 seconds and age group: 40-49 years; TMT A 58.57 vs 45 seconds; TMT B 162.43 vs 100 seconds). There was a significant association between duration of illness and scores of RAVLT1 and between age of onset of illness and RAVLTB scores (p<0.05). There was no significant association between scores of all tests with the type of treatment received by respondents. Conclusion: The proportion of neuro-cognitive impairment in patients with schizophrenia is very high (80%) and has major implications on the current management of schizophrenia in which this core symptom should also be a focus of treatment. The significant association between clinical factors and neuro-cognitive impairment highlights the importance of modifying those factors in order to minimise the deficit in patients with schizophrenia.